210k views
5 votes
Solve for c.

3abc + b = 5

c = (5 - b)/(3ab)
c = -5/3ab
c = 2 - ab

2 Answers

7 votes

Answer:

The answer to your question is: the first option

Explanation:

Equation 3abc + b = 5 solve for c

3abc = 5 - b pass b subtracting

3ac = (5 - b)/b pass b dividing

3c = (5 - b) / ab pass a dividing

c = (5 - b) / 3ab pass 3 dividing

User Benoit
by
5.1k points
4 votes

Answer:

the first one is correct

Explanation:

i took the test and it was correct

User Aleksandrbel
by
5.2k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.